2010
DOI: 10.12968/ijpn.2010.16.8.388
|View full text |Cite
|
Sign up to set email alerts
|

What does respite care mean for palliative care service users and carers? Messages from a conceptual mapping

Abstract: Over the coming years, as an ageing population with multiple chronic illnesses increases, the number of carers and paid carers is set to decrease. There is, therefore, an urgent need to understand what types of services are most supportive in helping to sustain caring relationships. Respite care is frequently mentioned as a key factor in supporting family carers and improving their quality of life but there is a lack of research to support its efficacy. This paper will present a conceptual map of respite care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…4,6 The needs of informal carers are significant but remain largely unmet. 7 These needs are best understood in the context of relationships, 8 yet the value of relationships as perceived by carers is underreported in the literature. 9 Life-limiting illness is often isolating for patients and carers alike, 10 many times leading to a burden of social loss.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 The needs of informal carers are significant but remain largely unmet. 7 These needs are best understood in the context of relationships, 8 yet the value of relationships as perceived by carers is underreported in the literature. 9 Life-limiting illness is often isolating for patients and carers alike, 10 many times leading to a burden of social loss.…”
Section: Introductionmentioning
confidence: 99%
“…The big question is to what degree palliative care and sitting service were prioritized in the municipality. Wolkowski et al (2010) have reported ambivalence toward providing respite care, where sitting service is a part. The reason was a lack of consensus concerning the aim for the service, that is, who would benefit from this service, the ill person or the caregiver, and which organization should take responsibility for providing this service.…”
Section: Preparedness For Deathmentioning
confidence: 99%
“…To prevent adverse effects of caregiving could be addressed by both informal and formal support (Grande et al, 2009). One requested and valued form of support for family caregivers is the sitting service (Shipman et al, 2005; Wolkowski et al, 2010; Ashworth & Baker, 2000). Sitting service in this study means support for the patient and family caregivers during a longer time than an ordinary care visit, offering help, support, and respite during the dying process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal caregivers to disabled people frequently report the need for short breaks, domestic help and respite care 3 . The 2010 EB adventure camp played an important role as respite care, helping informal caregivers to improve their quality of life while providing opportunities for the patients to experience active outdoor activities 4 …”
mentioning
confidence: 99%